Bioassay tests reveal for the first time pyrethroid resistance in Aedes mosquitoes from Franceville, southeast Gabon, Central Africa - Obame-Nkoghe Judicaël; Kondji Faël Moudoumi; Diouf El Hadji; Thiaw Omar; Niangui Brad Ghaven; Ondo-Oyono Arnauld; Okomo-Nguema Yasmine; Longo-Pendy Neil Michel; Mounioko Franck; Makanga Boris; Kamgang Basile; Paupy Christophe; et al. (Parasite, 2025)
The spread of resistance to insecticides, such as pyrethroids, in Aedes vectors increases the risk of spread of arboviral diseases. In Gabon, the insecticide resistance profiles of Ae. aegypti and Ae. albopictus species remain poorly known. During a study to monitor the dynamics of Aedes populations in Franceville, in south-east Gabon, the resistance profiles of these two species to pyrethroids, organophosphates and carbamates were assessed. Susceptibility tests on adults and synergist tests with piperonyl butoxide (PBO) were carried out as per the World Health Organization protocol. The results showed that Ae. aegypti and Ae. albopictus were susceptible to permethrin, pirimiphos-methyl and bendiocarb. However, both species were resistant to deltamethrin (mortality: 67% for Ae. aegypti; 33% for Ae. albopictus). Exposure to a 5-fold dose of deltamethrin increased mortality to 100% and 91% for Ae. aegypti and Ae. albopictus, respectively. Resistance to alpha-cypermethrin was also recorded (mortality: 82% for Ae. aegypti; 64.6% for Ae. albopictus). Pre-exposure to PBO resulted in the restoration of susceptibility to deltamethrin and alpha-cypermethrin for Ae. aegypti, and a significant increase in mortality for Ae. albopictus. These data provide the first evidence of pyrethroid resistance in Aedes in Gabon and could help to establish more effective control measures against arbovirus vectors.